Infraestructura kubernetes para implementación de aplicaciones en contenedores en entorno de pruebas en la Unidad De Tecnologías de la Información de la PUCE-IBARRA - Sánchez Villacis, Diana Abigail (2024)
This research addresses the implementation of a Kubernetes infrastructure for deploying containerized applications in a test environment within the Information Technology Unit of the Pontificia Universidad Católica del Ecuador, Ibarra (PUCE-Ibarra). The primary objective is to enhance operational efficiency and the quality of IT services through the use of Kubernetes, focusing on the portability, reliability, and availability of containerized applications. The study begins with a planning phase, where relevant information is collected and analyzed to design an appropriate cluster architecture. Available resources are evaluated, and the applications to be deployed are selected. Subsequently, the test environment is developed, including the installation and configuration of the operating system, Kubernetes, and additional tools for monitoring and container management. The delivery phase involves testing to validate the functionality of the cluster and its capacity to manage containerized applications. Finally, the formal transfer of the test environment to the IT department of PUCE-Ibarra is carried out, ensuring it is ready for operational use. The results demonstrate that the implementation of Kubernetes significantly improves the management of containerized applications, providing a more agile, scalable, and reliable environment. This solution benefits not only IT personnel but also faculty and students who rely on technological applications for their academic activities.